Listening Comprehension: Explicit Training on Listening Strategies in Beginning L2 Learners. - Azevedo, Aline Fay; BUCHWEITZ, Augusto (BELT - Brazilian English Language Teaching Journal, 2015)
The aim of the present study was to investigate the performance scores on a standardized proficiency exam after two months of explicit training on listening comprehension strategies. Two groups of adult learners of English as a foreign language (24 students in total) took part in this study. In the first part of the experiment the 24 participants of this study were subjected to a mock test to obtain their scores. In the second part of the experiment the experimental group (14 individuals in total) received two months (15 classes) of explicit training on listening comprehension strategies. The control group (10 individuals in total) did not have any explicit training on listening comprehension strategies. As expected, participants in the experimental group obtained different scores in the listening comprehension tasks of the proficiency exam after two months of explicit training. The study shows that explicit instructions and additional hours of specific training in the classroom can have a direct influence on students’ performance. The results corroborate the beliefs of Hedge (2007), Vandergrift (2004), Ur (1996) and Mendelsohn (1995), who believe that explicit training in listening strategies can be the key for beginning L2 students’ success in listening comprehension tasks.